Influence of freeze-drying and spray-drying preservation methods on survivability rate of different types of protectants encapsulated Lactobacillus acidophilus FTDC 3081 - Tang, Hock Wei; Sahar, Abbasiliasi; Paramasivam, Murugan; Tam, Yew Joon*; Ng, Hui Suan; Tan, Joo Shun (Taylor and Francis, 2020)
The aims of this study were to compare the effectiveness of different drying methods and to investigate the effects of adding a series of individual protectant such as skim milk, sucrose, maltodextrin, and corn starch for preserving Lactobacillus acidophilus FTDC 3081 cells during spray and freeze-drying and storage at different temperatures. Results showed a remarkable high survival rate of 70–80% immediately after spray- and freeze-drying in which the cell viability retained at the range of 109 to 1010 CFU/mL. After a month of storage, maltodextrin showed higher protective ability on both spray- and freeze-dried cells as compared to other protective agents at 4°C, 25°C, and 40°C. A complete loss in viability of spray-dried L. acidophilus FTDC 3081 was observed after a month at 40°C in the absence of protective agent.